Charging nanoparticle enhanced bio-based PCM in open cell metallic foams: An experimental investigation. (5th February 2019) - Al-Jethelah, M.; Ebadi, S.; Venkateshwar, K.; Tasnim, S.H.; Mahmud, S.; Dutta, A.
Highlights: The melting rate and stored energy were enhanced by increasing the supplied heat. Adding nanoparticles and metal foam accelerated the melting process by 57.5% The metal foam had more influence than the nanoparticles on the melting process. A uniform heat transfer is observed for lower porosity compared to higher porosity. Adding nanoparticles increases energy storage rate. Abstract: In this paper, an experimental investigation is carried out to examine the melting process of nanoparticle enhanced phase change material (i.e., nano-PCM) inside a metal foam enclosure under constant heat flux boundary condition. Visualization experiments were carried out using a bio-based nano-PCM (i.e., copper oxide (CuO) nanoparticles dispersed in the bio-based coconut oil PCM) inside an open-cell metal foam. Rectangular blocks, made from aluminium metal foam of pore density of 5 PPI and porosities of 88%, 92%, and 96%, were considered. An experimental setup was constructed to track the evolution of the melting process and observe the transient variation in temperature. Temperatures were measured at selected locations inside the nano-PCM filled metal foam. Melt fraction was calculated by means of image analysis. Experimentally obtained images corresponding to the melting process of PCM, nano-PCM, PCM in metal foam, and nano-PCM in metal foam are presented for selected times and applied wall heat fluxes. Corresponding melt fractions and energy storage rates are calculated and presented as well. The results showed that utilizing both nanoparticles and metal foam increase the melting and energy storage rates. The results further show uniform melting for low porosity (88%) porous medium as heat is transferred primarily by conduction. For high porosity (96%) porous medium, non-uniform melting, e.g., more melting at the upper part compared to the lower part is observed as heat is transferred by convection at the upper part and by conduction at the lower part. Outcome of the current research can potentially be applied to latent heat thermal energy storage systems, hybrid-electric vehicles' rechargeable prismatic-battery thermal management systems, and electronic cooling systems in remote locations. The melting process is enhanced by 1.2% when nanoparticles were added to the PCM; however, higher enhancement was observed, i. e. 41.2%, when the metal foam was embedded in the pure PCM at 1814 W/m 2 and 2160 s. The energy stored rate accelerated by utilizing the metal foam in comparison with the pure PCM and the nano-PCM, i. e. 2.61% by adding nanoparticles and 28.81% by utilizing the metal foam at 2835 W/m 2 and 2280 s.